Pragmatic Trials in Long‐Term Care: Implementation and Dissemination Challenges and Opportunities. Issue 3 (23rd February 2022) - Levy, Cari; Zimmerman, Sheryl; Mor, Vincent; Gifford, David; Greenberg, Sherry A.; Klinger, Juliet Holt; Lieblich, Cathy; Linnebur, Sunny; McAllister, Angie; Nazir, Arif; Pace, Douglas; Stone, Robyn; et al.
Abstract: Randomized controlled trials are considered the most rigorous research design in efficacy and effectiveness research; however, such trials present numerous challenges that limit their applicability in real‐world settings. As a consequence, pragmatic trials are increasingly viewed as a research design that overcomes some of these barriers with the potential to produce findings that are more reproducible. Although pragmatic methodology in long‐term care is receiving increasing attention as an approach to improve successful dissemination and implementation, pragmatic trials present complexities of their own. To address these complexities and related issues, experts with experience conducting pragmatic trials, developing nursing home policy, participating in advocacy efforts, and providing clinical care in long‐term care settings participated in a virtual consensus conference funded by the National Institute on Aging in Spring 2021. Participants identified 4 cross‐cutting principles key to dissemination and implementation of pragmatic trial interventions: (1) stakeholder engagement, (2) diversity and inclusion, (3) organizational strain and readiness, and (4) learn from adaptations. Participants emphasized that implementation processes must be grounded in the perspectives of the people who will ultimately be responsible for implementing the intervention once it is proven to be effective. In addition, messaging must speak to long‐term care staff and all others who have a stake in its outcomes. Although our understanding of dissemination and implementation strategies remains underdeveloped, this article is designed to guide long‐term care researchers and community providers who are increasingly aware of the need for pragmatism in disseminating and implementing evidence‐based care interventions. Abstract : See related editorial by Zimmerman et al . and Special Articles by Gurwitz et al . and Resnick et al . in this issue.